Assessment of glomerular morphological patterns by deep learning algorithms - Weis, Cleo-Aron Thias; Bindzus, Jan Niklas; Voigt, Jonas; Runz, Marlen; Hetjens, Svetlana; Gaida, Matthias; Popovic, Zoran V.; Porubský, Štefan (Journal of nephrology, 2022)
Compilation of different morphological lesion signatures is characteristic of renal pathology. Previous studies have documented the potential value of artificial intelligence (AI) in recognizing relatively clear-cut glomerular structures and patterns, such as segmental or global sclerosis or mesangial hypercellularity. This study aimed to test the capacity of deep learning algorithms to recognize complex glomerular structural changes that reflect common diagnostic dilemmas in nephropathology.
Gesehen am 07.02.2022